PENGARUH STRATEGI PEMBELAJARAN TUTOR SEBAYA TERHADAP HASIL BELAJAR FIQH MATERI THAHARAH SISWA KELAS VII MTS ULUMUL QUR’AN KECAMATAN MEDAN KOTA TAHUN PEMBELAJARAN 2019/2020 - Kurniawansyah, Kurniawansyah (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2020)
This study aims to determine the learning outcomes of the Thaharah material Fiqh before and after using peer tutor learning strategies, as well as the influence of peer tutor learning strategies on the learning outcomes of class VII students of Islamic Law and Islamic Thaharah material at MTs Ulumul Qur'an Medan Kota district in the 2019/2020 learning year. The population in this study were all students of class VII as many as 34 students. The entire population was determined as the research sample. This research method is an experimental method. The data collection tool used was a test of learning outcomes of the Thaharah material Fiqh in the form of multiple choice objective questions as many as 20 questions that were tested before and after participating in the learning using peer tutor learning strategies. The conclusions obtained from this study are: the learning outcomes of Thaharah material Fiqh before using the tutor learning strategy are 65.59 category C (sufficient), the learning outcomes of Thaharah material Fiqh learning after using peer tutor learning strategies are 80.59 category A (very good). The effect of peer tutor learning strategies on learning outcomes of thaharah material for class VII MTs Ulumul Qur'an Medan Kota sub-district for the 2019/2020 learning year was 43.59%. Peer tutor learning strategies have a significant effect on improving students' understanding of the Islamic Law (Fiqh) material. The price of tcount = 8.242 is greater than t table at α = 0.05 db = n1 + n2 - 2 or 34 + 34 - 2 = 66, namely 8.242 1.668 so that the better the use of the Peer Tutor learning strategy, the more it will increase students' understanding of Fiqh, especially about the Thaharah material.